(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Demonetization is the strongest policy that is used against many illegal elements such as corruption and inflation to reform the economy. The concept of Demonetization is not new almost across the globe has adopted Demonization to upgrade their financial system. India adopted the Demonetization three times: first in January 12, 1946, and second January 16, 1978. But the term Demonetization became well known on November 8, 2016 when P.M. Narendra Modi suddenly demonetized the Rs. 500 and Rs.1000 bank notes of Mahatma Gandhi series with the prime objective to curb the black money and counterfiet currency. This monetary step shaked each segment of economy in which banking performance was significantly affected. Their depositposition, Advance Policy, NPAs and Liquidity were impacted at some or large scale. Therefore, the present study has analysed the impact of demonetization on the performance of banks (with special reference to Uttarakhand) and found that there is no significant impact of demonetization on the overall performance of banks in Uttarakhand State.